Perancangan Model Interaksi Manusia dan Komputer untuk Mewujudkan Printer Otomatis Berbasis Pemrograman - Heri Santoso (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2025)
The development of human-computer interaction (HCI) technology has undergone significant transformations along with the increasing need for efficient automation systems. This research aims to design a human-computer interaction model capable of operating a printer automatically without manual intervention. Through a programming approach based on voice commands and system input detection, this design is expected to achieve printer performance that is adaptive to user commands. The research methods used include system requirements analysis, interactive interface design, implementation of Python programming algorithms, and testing of automatic printer performance. The results show that the designed system is capable of executing print commands through voice input and program commands with a 90% success rate, and an average response time of 3-5 seconds. These findings demonstrate that the application of the HCI programming-based concept can optimize the document printing process efficiently, ergonomically, and innovatively